2022
DOI: 10.19086/aic.2022.3
|View full text |Cite
|
Sign up to set email alerts
|

Transversal factors and spanning trees

Abstract: Since the proof of a "colorful" version of [Caratheodory's theorem](https://en.wikipedia.org/wiki/Carath%C3%A9odory%27s_theorem_%28convex_hull%29) by Bárány in 1982, it has been an important problem to obtain colorful extensions of other classical results in discrete geometry (for instance Tverberg's theorem). The present paper continues this line of research, but in the context of extremal graph theory rather than discrete geometry. Mantel's classical theorem from 1907 states that every $n$-vertex graph on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 21 publications
(24 reference statements)
0
30
0
Order By: Relevance
“…Inspired by a series of very recent successes on rainbow matchings [29,28,30,31], rainbow Hamilton cycles [8,9,21] and rainbow factors [7,12,33], we suspect the threshold for a rainbow spanning subgraph in (hyper)graph system is asymptotically same with the threshold for a spanning subgraph in a (hyper)graph.…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by a series of very recent successes on rainbow matchings [29,28,30,31], rainbow Hamilton cycles [8,9,21] and rainbow factors [7,12,33], we suspect the threshold for a rainbow spanning subgraph in (hyper)graph system is asymptotically same with the threshold for a spanning subgraph in a (hyper)graph.…”
Section: Discussionmentioning
confidence: 99%
“…Note that this lemma is not stated exactly as above in [30]. For completeness, we deduce it from the lemma below stated in [30]. Proof of Lemma 2.21.…”
Section: Graph Systemsmentioning
confidence: 95%
“…[h] the η-fraction graph of the graph system G. This concept of fraction graph was introduced in [30] by Montgomery, Müyesser and Pehova. They observed that this concept is very useful for finding graph partial transversals.…”
Section: Graph Systemsmentioning
confidence: 99%
See 2 more Smart Citations